Hubungan Pekerjaan dan Peran Pengawas Menelan Obat Terhadap Keberhasilan Pengobatan Tuberkulosis di Kota Kupang - Etty Dedy, Maria Agnes; Sagita, Sidarta; Artawan, I Made (Cerdika: Jurnal Ilmiah Indonesia, 2022)
Tuberculosis is the second leading cause of death from infectious diseases in the world and Indonesia ranks third in the country with the highest burden of TB that can affect the success of treatment is the role of the Drug Swallowing Supervisor (PMO) in helping pulmonary TB patients to recover. Pulmonary TB treatment takes time which is very long, to ensure regularity of treatment required a PMO who will help sufferers during the treatment phase. World Health Recommendations Organization (WHO) in the Directly Observed Treatment Shortcourse (DOTS) strategy for TB control since 1995 is the involvement of PMO. PMO's Role It is very important for adherence and regularity to take medication to achieve healing, prevent transmission and avoid cases of drug resistance. The purpose of this research is to determine the relationship between the role of PMO on the success of treatment of pulmonary TB patients in Indonesia Kupang City. This research method is a research with observational method analytic and cross sectional approach. The population in the study includes all patients Pulmonary TB who has completed treatment in Kupang City. The sample is 79 sample, taken using probability sampling technique. The results of the Chi Square test results obtained p-value: 0.000 (p 0.05). The conclusion of this study is that there is a relationship between the role of PMO on the success of treatment of pulmonary TB patients in Kupang City